How to grade items for a question bank and rank tests based on student performance - Thomas, Puthiaparampil; Md Mizanur, Rahman; Henry Rantai, Gudum; Brohi, Imam Bux; Fong, Isabel Lim; Rosalia, Saimon (MedEdPublish, 2020)
Introduction: Not utilising post-test psychometric analyses of questions, and not maintaining a question bank seemed to adversely affect the quality of tests and increase the workload of academicians, as they are required to write fresh questions for all examinations. The literature review did not reveal any gold standard method for creating a question bank. This study has formulated criteria for recruiting multiple choice questions for a question bank and introduced a formula to rank whole tests.